An adaptive fault-tolerant control scheme for a class of fractional-order systems with unknown input dead-zones. Issue 2 (25th January 2021) - Wang, Caiyun; Liu, Xiaoping; Wang, Huanqing
Abstract : An adaptive backstepping fault-tolerant control scheme is presented for a class of fractional-order systems in the presence of unknown input dead-zones. The proposed fault-tolerant control scheme ensures all the closed-loop signals are bounded ultimately. Especially, the tracking error can be made as small as possible by choosing appropriate design parameters. Furthermore, this scheme not only works for fractional-order systems with unknown linear terms but also works for these with unknown nonlinear terms. Finally, several practical examples are simulated to verify the effectiveness of the proposed fault-tolerant control scheme.